Shuangdong Capsule Activates Insulin Signal Pathway to Improve Urinary Tract Infection in Diabetic Rats - Zhao, Cong; Wang, Bin; Mu, Qi-xiang; Wu, Jun; Cheng, Zhen-han; Liu, Qing; Li, Hai-song; Wang, Ji-sheng (Combinatorial Chemistry & High Throughput Screening, 2025)
Background and Aim Diabetes and Urinary Tract Infections (UTIs) are both common and serious health problems. Shuangdong capsule, a Chinese patent medicine, has been used to treat these conditions. This study assesses its efficacy and mechanism in treating diabetes combined with UTIs. Methods We induced diabetes in rats using streptozotocin and UTIs with Escherichia coli, dividing the rats into five groups: control, model, levofloxacin, Shuangdong capsule, and levofloxacin + Shuangdong capsule. After two weeks, we measured blood glucose, insulin, infection indicators, and bladder histology. We also detected the expression of insulin receptor substrate 1 (IRS1)-phosphoinositide 3-kinase (PI3K)-protein kinase B (Akt)-C-X-C motif chemokine ligand 2 (CXCL2) signaling pathway by Western Blot and the myeloperoxidase (MPO) levels by Enzyme-Linked Immunosorbent Assay (ELISA). Additionally, we conducted a Mendelian randomization study using genetic variants of the insulin receptor to assess its causal effect on UTI risk. Results Shuangdong capsule improved bladder pathology and infection indicators, similar to levofloxacin. It did not affect blood glucose or insulin levels. Moreover, it reversed the suppression of the IRS1-PI3K-Akt-CXCL2 pathway and MPO levels caused by UTI in diabetic rats. The Mendelian randomization study showed that increased insulin receptor expression reduced UTI risk, which was consistent with the results of the animal experiments. Conclusion The Shuangdong capsule was effective in treating diabetes with UTIs. It may function by activating the IRS1-PI3K-Akt signaling pathway, thereby increasing CXCL2 and MPO levels, enhancing innate immunity, and promoting bacterial clearance. The Mendelian randomization study provided further evidence supporting the causal role of the insulin receptor in UTI prevention.
Keywords: bacterial infection